Photosynthesis at an extreme end of the leaf trait spectrum how does it relate to high leaf dry mass per area and associated structural parameters? - Hassiotou, Foteini (Journal of experimental botany, 2010)
Leaf dry mass per area (LMA) is a composite parameter relating to a suite of structural traits that have the potential to influence photosynthesis. However, the extent to which each of these traits contributes to variation in LMA and photosynthetic rates is not well understood, especially at the high end of the LMA spectrum. In this study, the genus Banksia (Proteaceae) was chosen as a model group, and key structural traits such as LMA, leaf thickness, and density were measured in 49 species. Based on the leaf trait variation obtained, a subset of 18 species displaying a wide range in LMA of 134-507 g m(-2) was selected for analyses of relationships between leaf structural and photosynthetic characteristics. High LMA was associated with more structural tissue, lower mass-based chlorophyll and nitrogen concentrations, and therefore lower mass-based photosynthesis. In contrast, area-based photosynthesis did not correlate with LMA, despite mesophyll volume per area increasing with increases in LMA. Photosynthetic rate per unit mesophyll volume declined with increasing LMA, which is possibly associated with structural limitations and, to a lesser extent, with lower nitrogen allocation. Mesophyll cell wall thickness significantly increased with LMA, which would contribute to lower mesophyll conductance at high LMA. Photosynthetic nitrogen use efficiency and the nitrogen allocation to Rubisco and thylakoids tended to decrease at high LMA. The interplay between anatomy and physiology renders area-based photosynthesis independent of LMA in Banksia species